MdERF1B-MdMYC2 module integrate ethylene and jasmonic acid to regulate the biosynthesis of anthocyanin in apple. Issue 1 (23rd June 2022) - Wang, Shuo; Li, Li-Xian; Fang, Yue; Li, Dan; Mao, Zuolin; Zhu, Zihao; Chen, Xue-Sen; Feng, Shou-Qian
Abstract: Ethylene (ET) and jasmonic acid (JA) are crucial hormones that promote anthocyanin synthesis in apple ( Malus × domestica ) . However, the mechanism by which these hormones cooperate to modulate anthocyanin production in apple is unclear. According to our results, MdERF1B expression was strongly induced by ET and JA. Physiological phenotypes and the results of molecular biological analyses indicated that MdERF1B encodes a positive regulator of anthocyanin synthesis. Specifically, MdERF1B was capable of combining directly with MdMYC2 promoter for promoting gene levels. Additionally, MdERF1B interacted with two JA signaling pathway inhibitors, namely MdJAZ5 and MdJAZ10. The MdERF1B–MdJAZ5/10 protein complex decreased the ability of MdERF1B to activate the MdMYC2 promoter. Furthermore, MdEIL1, which is a crucial protein for ET signal transduction, was observed to bind directly to the MdERF1B promoter, thereby upregulating gene expression. These results suggest that MdERF1B is a core gene responsive to JA and ET signals. The encoded protein, together with MdMYC2, MdJAZ5/10, and MdEIL1, modulate anthocyanin synthesis in apple. This study clarifies the synergistic mechanism by which JA and ET regulate anthocyanin production in apple.